The Effect of Sodium Hydroxide Absorbent on The Exhaust Emissions From Internal Combustion Engine: - Ilham Zainul Arifin; Wirawan Wirawan; Hari Rarindo (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Exhaust emissions are the residue from burning fuel which can cause air pollution. To overcome this problem, it is necessary to design a system for reducing exhaust emissions of internal combustion engine. This study aims to determine the effect of absorbent concentration on the exhaust emission from internal combustion engine. The research was carried out in 2 stages, namely designing a system for reducing exhaust emissions from internal combustion engines and processing exhaust emissions by channeling exhaust emissions into an exhaust emission reduction system. The internal combustion engine used pertalite. The exhaust emissions consisted of CO, CO2 and HC. The absorbent concentrations were 0.05 M, 0.1 M and 0.15 M. The engine speeds were 800, 1000, 1500 and 2000 rpm. The paired-t test showed that the exhaust emission reduction system in this study can reduce exhaust emission. The one-way Anova test resulted the absorbent concentration affect the exhaust gas emissions, both CO, CO2 and HC which are expressed in the efficiency of reducing exhaust emission.. The greatest efficiency in reducing exhaust emission is CO2 of 67.95%. The lowest efficiency of reducing exhaust emission is CO, which is 46.92%, while the efficiency of reducing HC emission is 62.47%.